MERANCANG LEMBAGA KEUANGAN MIKRO SYARIAH YANG TEPAT PADA DESA PASAREAN, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Trihantana, Rully; Mursyidah, Azizah; Santika, Ika (SAHID DEVELOPMENT JOURNAL : Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah, 2024)
MFIs are Financial Institutions that are oriented towards improving the welfare of members and the community. The birth of Sharia Microfinance Institutions in Indonesia is one of the answers to see the development of Sharia Banking which is still centralized to the upper middle class. while in Pasarean Village, most of the people have income from agriculture, plantations and MSMEs. This counseling and socialization service activity regarding Sharia Microfinance Institutions was carried out at the Pasarean Village Office, Pamijahan District, Regency, Bogor Jawa Barat. The target of this PKM activity is adults, especially investors. This activity is carried out face-to-face (On the spot training) which begins with observation and coordination and licensing with the local Village Head regarding the plan of activities to be carried out in the environment regarding the availability of places, times, and participants. Service activities are carried out using several stages, namely preparation, socializationon Sharia Microfinance Institutions and reporting. The method used in the implementation of PKM activities is socialization with counseling techniques in the form of lectures or presenting material in the form of theory and short film videos related to the theme we take, questions and answers and discussions. The results of the activity show an increase in public understanding and awareness of Sharia Microfinance Institutions.